2017
DOI: 10.1186/s12885-017-3063-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic histological factors in patients with esophageal squamous cell carcinoma after preoperative chemoradiation followed by surgery

Abstract: BackgroundPathological response is an important marker for tumor aggressiveness in patients with esophageal squamous cell carcinoma (ESCC) who receive preoperative chemoradiation followed by esophagectomy. We aim to evaluate the prognostic value of histological factors after trimodality treatments.Methods91 patients who received preoperative chemoradiation followed by transthoracic esophagectomy between 2009 and 2014 were included. The pathological examination was reviewed. Overall survival and disease free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…As a routine examination, CECT is a useful tool for differential diagnosis, preoperative evaluation, treatment, and prognosis of patients with esophageal cancer (30,31,(42)(43)(44)(45). The significance of the present study is that it proposes a novel method for predicting LVI in ESCC for the first time.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As a routine examination, CECT is a useful tool for differential diagnosis, preoperative evaluation, treatment, and prognosis of patients with esophageal cancer (30,31,(42)(43)(44)(45). The significance of the present study is that it proposes a novel method for predicting LVI in ESCC for the first time.…”
Section: Discussionmentioning
confidence: 91%
“…Pathological studies have now incorporated LVI into the TNM staging system for multiple cancers (46,47). Many studies have revealed that LVI is an independent risk factor for survival in patients with ESCC (44,48). Preoperative prediction of LVI status is necessary for patients to implement an aggressive treatment plan (49).…”
Section: Discussionmentioning
confidence: 99%
“…Lagarde et al and Tu et al concluded that the presence of PNI had an adverse impact on survival time. 26,27 In addition, we found that LVI was independently associated with a shorter DFS. Previous studies by Lagarde et al and Gu et al proposed that LVI was an indicator of adverse prognosis.…”
Section: Discussionmentioning
confidence: 54%
“…Lymphatic and venous invasion are independent prognostic factors for survival after initial surgical resection of ESCC (26- 28) and after neoadjuvant therapy followed by surgery (29)(30)(31). Among these reports, lymphovascular invasion had prognostic value in patients with ESCC treated by NCRT followed by surgery, which are the same histological type and treatment modality as the present study (30,31). Therefore, lymphatic/vascular invasion is very important for the prognosis of esophageal cancer, not only after surgery, but also after neoadjuvant therapy followed by surgery.…”
Section: Various Clinicopathological Factors Have Been Reported As Risky For Early Recurrence or Cancer Death In Patients Withmentioning
confidence: 99%